Analysis The Message of Da'wah in The Hati Suhita Film With A Roland Barthes Semiotic Approach: Perspectives of Morality, Sharia, and Faith - Choirizah, Adinda; Rozi, Fakhrur (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2025)
This study analyzes the da'wah messages in the film Hati Suhita using Roland Barthes' semiotic approach to explore the meanings of denotation, connotation, and myth in five key scenes. This research employs a qualitative method with a semiotic analysis technique that focuses on visual signs, dialogues, and symbols in the film to interpret the conveyed da'wah messages. Data were collected through film observation and documentation of scenes containing da'wah elements. The film portrays the struggles of a young woman named Suhita in facing the challenges of an arranged marriage, emotional turmoil, and the search for true love within the bonds of marriage. The findings indicate that the film effectively conveys da'wah messages about sacrifice, patience, sincerity, and the importance of communication in family life. Additionally, the film emphasizes the role of women in maintaining self-respect and marital happiness within an Islamic context. The novelty of this research lies in the application of semiotic analysis to understand da'wah messages in film as a medium for conveying Islamic values relevant to contemporary issues. This study provides a significant contribution to da'wah studies through film media, which serves as a bridge between Islamic values and the challenges of modern life.